DARE Newsletter, Vol. 4, No. 1, Winter 2001 - DARE; Carlson, David; Simon, David (Dictionary of American Regional English, 2001)
Contents: "Notes from the City: An Urban Fieldworker's Experience" by David Carlson; "Funding Update" by David Simon; "Staff Member Profile: Beth Gardner"; "Contributors to DARE in 2000"; "Coming in Volume IV"; "Ask a Fieldworker: August Rubrecht, Patt VanDyke"; "Notes and Quotes"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Fieldwork; Lexicography; Regional English; English Language -- Dialects -- United States